West African Economic and Monetary Union (WAEMU) : Common Policies for Member Countries. (IMF Staff Country Reports; Country Report, 2018)
This report reviews the discussions between the IMF and the regional institutions of the West African Economic and Monetary Union (WAEMU). It highlights that the economic activity in the WAEMU remains strong but vulnerabilities persist. Despite lower terms of trade, social tensions, and security challenges within the region, real GDP growth is estimated to have exceeded 6 percent in 2017, underpinned by strong domestic demand. The outlook remains positive but hinges critically on the planned fiscal consolidation and implementation of structural reforms by member countries. Growth is projected to stay above 6 percent with continued low inflation over the medium term. Risks are tilted to the downside.